Chloroplast Genomic Resources and Genetic Divergence of Endangered Species Bretschneidera sinensis (Bretschneideraceae) - Shang, Ce; Li, Enze; Yu, Zhucheng; Lian, Mengjia; Chen, Zhuo; Liu, Kangjia; Xu, Linli; Tong, Zhe; Wang, Meifang; Dong, Wenpan (Frontiers in Ecology and Evolution, 2022)
Bretschneidera sinensis is an endangered woody species found in East and South China. Comprehensive intraspecies chloroplast genome studies have demonstrated novel genetic resources to assess the genetic variation and diversity of this species. Using genome skimming method, we assembled the whole chloroplast genome of 12 genotypes of B. sinensis from different geographical locations, covering most wild populations. The B. sinensis chloroplast genome size ranged from 158,959 to 159,045 bp and displayed a typical circular quadripartite structure. Comparative analyses of 12 B. sinensis chloroplast genome revealed 33 polymorphic SSRs, 105 polymorphic SNPs, and 55 indels. Phylogenetic analysis showed that the 12 genotypes were grouped into two branches, which consistent with the geographical distribution (Eastern clade and Western clade). Divergence time estimates showed that the two clades were divergent from 0.6 Ma in the late Pleistocene. Ex situ conservation is essential for this species. In this study, we identified SNPs, indels, and microsatellites of B. sinensis by comparative analyses of chloroplast genomes and determined genetic variation between populations using these genomic markers. Chloroplast genomic resources are also important for further domestication, population genetic, and phylogenetic analysis, possibly in combination with molecular makers of mitochondrial and/or nuclear genomes.